2009
DOI: 10.1177/0042098009346862
|View full text |Cite
|
Sign up to set email alerts
|

How Diverse Are US Suburbs?

Abstract: American suburbs are popularly perceived as demographically homogeneous compared with central cities. Social scientists have long challenged this perception; indeed, some cite recent evidence on suburban diversity to assert that the suburb—city distinction has become irrelevant. Here, several conceptual, methodological and theoretical improvements are introduced to improve the adjudication of claims about the extent and nature of suburban diversity. The analysis examines patterns and potential antecedents of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 39 publications
(48 reference statements)
2
49
0
Order By: Relevance
“…Recent studies have identified that the dichotomy of black, poor cities and white wealthy suburbs has been, slowly, and now more rapidly, and steadily, changing. Many scholars have found that suburbs are becoming more diversified in certain dimensions (Hall and Lee, 2010;Lang, 2003b;.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent studies have identified that the dichotomy of black, poor cities and white wealthy suburbs has been, slowly, and now more rapidly, and steadily, changing. Many scholars have found that suburbs are becoming more diversified in certain dimensions (Hall and Lee, 2010;Lang, 2003b;.…”
Section: Discussionmentioning
confidence: 99%
“…Bigger metropolitan areas have more internal differentiation and are traditionally much more diverse than smaller ones (Pendall and Carruthers, 2003). Certain dimensions of suburban diversity are found to increase with the size of their constituent metropolitan areas (Hall and Lee, 2009). Thus, larger metropolitan areas are expected to have greater levels of suburban diversity.…”
Section: A Multiple Linear Regressionmentioning
confidence: 97%
See 3 more Smart Citations